Business Intelligence : the Effectiveness of Strategic Intelligence and Its Impact on the Performance of Organizations. - Cohen, Corine (ISTE., 2013)
Following a long process of qualitative, quantitative, and empirical research next to Strategic Intelligence (SI) experts and large companies, this book proposes a way to improve SI and its impact on the performance of an organization. From an exploration, description and evaluation model of SI, a measurement tool in two parts has been built. For all kind of firms and all advancement levels of SI, it explains the construction of a control panel which can be used to pilot SI and its impact on the performance of an organization.